Reformasi Birokrasi: Antara Netralitas Politik Dan Tuntutan Pelayanan Publik - Noer, Hamka Hendra (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2018)
Bureaucratic reformation ultimately seen as part of an overall reform of the post New Order government. First of all, to establish a neutral bureaucracy of politics. Second of all, to improve services as a public service institution. In the case of a neutral bureaucratic, politics has brought signi cant results. In the general election three times (in 1999, 2004, and 2009), the involvement and mobilization of political support through the bureaucracy was lesser compare to what happened during the New Order government. However, the attempts to do politicized bureaucracy snaking is unavoidable. Firstly, with regard to the nature of bureaucracy that can not be separated from the need to ght for its own interests—in addition to providing public services. Secondly, there is an involment from the political of cials. On the other hand, the attempts to perform public service continued through the decentralization policy. Although in general, decentralization policies have not been able to encourage or strengthen the public services carried out by the bureaucracy. Bureaucratic reformation in Indonesia, requires a long time to complete. Wishing that in order to have a professional bureaucracy and enabling better public services, may not be realized in a short time.